IMPLEMENTASI LAYANAN WHISTLEBLOWING SYSTEM DI INSPEKTORAT KABUPATEN REMBANG - Kristiawan, Daffa Aulya; Hanani, Retna; ., Kismartini (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
The public complaint service is a form of government policy to increase agency accountability in providing service to the community. One of the agencies that has implemented an online-based public complaint service is the Rembang Regency Inspectorate in the form of a Whistleblowing system. This research aims to analyze the implementation of Whistleblowing system services, as well as the elements that support or hinder its implementation. This research uses a descriptive approach using qualitative strategies. This research result show that implementation of the Whistleblowing system is not optimal due to the lack of complaint reports from the public. The driving factors in implementing the Whistleblowing system service at the Rembang Regency Inspectorate are the quality of the implementers and the bureaucratic structure. The obstacles faced include communication, authority, financial and human resource constraints. It can be concluded that the implementation of the Whistleblowing system service at the Rembang Regency Inspectorate as a whole has gone well, but several inhibiting factors have caused the implementation of the program to be less than optimal. Suggestions from researchers are implementing a special forum to introduce complaint services, shifting the previously conventional complaint system to now using Whistleblowing system services, adding employees in other work units, using outsourching services for updates, optimizing employees to update the Whistleblowing system, lobbying with BKD employee considerations.